Competitive marketing strategy : dynamic manoeuvring for competitive position - Brown, Linden. (Nelson, 1997)
This book is divided into seven parts: The competitive marketing strategy framework; Dominant position strategies; Market leader strategies; Challenger and follower strategies for repositioning as a major force; Growth strategies for niche competitors; Competitive international marketing strategies; Strategy evaluation; Implementation and Review.